ANALISIS NILAI ERGONOMIS DAN ESTETIKA PADA PERANCANGAN NOKEN PAPUA - Federika Mandacan; Hahury, Sanny; Masniar, Masniar; Gani, Mardiah; Kayatun, Siti Nur (Industrial Engineering Journal – System, 2023)
Seeing the development and fashion needs of the people in the city of Manokwari, especially for the indigenous Arfak people, researchers tried to meet this community's needs by designing noken with motifs and colors from the traditional arrangements of the native Arfak people. Visual analysis will be used in conducting the evaluation. The examination is carried out directly based on an assessment of the product produced by providing a specific explanation regarding the ergonomic and aesthetic elements inherent in the product. No particular standards are used in the analysis because this research analyzes products that do not have standard measures in their processing or use. Meanwhile, to determine the level of public satisfaction with the noken designed by researchers, a questionnaire was used for several people who were used as samples for decision-making. The sample size was determined using the Slovin formula, then the questionnaire was analyzed using Microsoft Excel. Based on the discussion results, designing an ergonomic Papuan noken was carried out by paying attention to several influencing factors: security, comfort and flexibility. In contrast, creating an aesthetic Papuan noken was carried out by paying attention to several influencing factors, namely artistic, cultural, and religious values. The level of public satisfaction with the new Papuan noken design by researchers reached 76%, 78% from the ergonomic side and 75% from the aesthetic side.